Diurnal Variability of Peak Expiratory Flow Rate in Healthy Adult Employees of a Medical College of Kathmandu - Khakurel, Gita; Gautam, Kalyan; Chalise, Sanat (Journal of Institute of Medicine Nepal, 2021)
Introduction Peak expiratory flow measurement is a simple measure of respiratory capacity to diagnose airflow obstruction and monitor treatment response in patients with pulmonary diseases. But there is wide diurnal variability in its values. The objectives of this study was to determine the diurnal variability of peak expiratory flow rate in healthy adults. Methods This cross-sectional study was done in employees of Kathmandu Medical College, Duwakot between March to August 2020. A total of 74 subjects of 30-45 years were included in the study. After adequate training, subjects were asked to record their own peak expiratory flow five times a day by Mini-Wright peak flow meter. Diurnal variability was expressed as amplitude percent mean and standard deviation percent mean. Data analysis was done by student’s unpaired t-test and one-way ANOVA. Results The mean peak expiratory flow rate (in L/min) were lowest in morning (male: 478.75±45.91; female: 362.86±20.51) followed by progressive rise throughout the day and highest at evening (male: 531.88 ±43.95; female: 415.71±20.97) with slight fall at bedtime (male: 486.88±46.38; female: 362.86±20.51). The difference in peak expiratory flow rate at different time periods was statistically significant in both males and females (p<0.001). The diurnal variability as calculated by amplitude percent mean and standard deviation percent mean were found to be significantly higher in females (p=0.001 and 0.004 respectively). Conclusion There is a variation of peak expiratory flow rate recorded during different time points of the day in healthy adults.